Evidences of Accountability Process Substantiation from Sīrah and its Comparison to the Duties of Federal Ombudsman in Pakistani Context - Muhammad Ikramullah; Khan, Muhammad Hayat (Journal of Islamic and Religious Studies, 2019)
In any society, the administration has the status of a pillar, and its good or bad move directly impacts society. There are institutions to compensate public complaints on government initiatives in many countries of the world that keep check on government administrations. For this purpose "Federal Ombudsman" was established in Pakistan. The main responsibilities of this institution include the execution to enjoin the right and forbid the wrong (Amr bil Ma’rūf wal Nahi ‘An al Munkar), monitoring government employees in administrative matters, hearing the complaints of the public against organizations and preventing them from violating individual rights. In this article, it has been reviewed that how we can seek guidance from the Sīrah of the Prophet (P.B.U.H) is in this matter, to evaluate the present system of "Federal Ombudsman". In addition, the main responsibilities of the "Federal Ombudsman" were discussed in the article. In conclusion recommendations have been made for further improvement.